Impact of Growing Media and Nutrition on Growth and Yield of Broccoli Microgreens (Brassica oleracea) - Khairunnisa, Noviandani; Warnita, Warnita; Hervani, Dini (International Journal of Environment, Agriculture and Biotechnology, 2023)
Microgreens are a new class of vegetables that are harvested within 7-21 days after sowing, have a lot of nutritional potential and are a new trend in the food industry. One type of microgreens that is grown commercially is broccoli. The nutrients in broccoli microgreens are 4-6 times more than mature plants, contain good vitamin C, and contain antioxidants that can help protect the body from the harmful effects of free radicals. Cultivating microgreens requires the right planting medium and nutrients to support plant growth. The research objective was to obtain the interaction between the types of growing media and the nutrients used to increase the growth and yield of broccoli microgreens. This research was carried out from October to November 2022 at the Greenhouse of the Faculty of Agriculture, Andalas University. The study was a two-factorial experiment in a completely randomized design (CRD) with 3 replications. The first factor is several types of planting media, namely soil, cocopeat, and rock wool. The second factor consisted of several types of nutrition, namely AB mix and young coconut water. Observational data were analyzed using statistical analysis of variance test F. If F Count treatment is greater than F Table 5% then it will be continued with the DNMRT test at 5% level. The results showed that there was an interaction between the type of growing media and the nutrition given to the growth of broccoli microgreens. The use of rock wool growing media and AB mix nutrition gave the best response for the observed parameters of seedling height, number of leaves, fresh weight, and chlorophyll content. The results of the antioxidant analysis carried out when harvesting broccoli microgreens gave a red color change when given HCl, whereas if NaOH was added drop by drop there was no blue color change. So it can be concluded that broccoli microgreens contain betacyanin.